Comparison of the pathogenicity of Nipah virus isolates from Bangladesh and Malaysia in the Syrian hamster. - Blair L DeBuysscher; Emmie de Wit; Vincent J Munster; Dana Scott; Heinz Feldmann; Joseph Prescott (Public Library of Science (PLoS), 2013)
Nipah virus is a zoonotic pathogen that causes severe disease in humans. The mechanisms of pathogenesis are not well described. The first Nipah virus outbreak occurred in Malaysia, where human disease had a strong neurological component. Subsequent outbreaks have occurred in Bangladesh and India and transmission and disease processes in these outbreaks appear to be different from those of the Malaysian outbreak. Until this point, virtually all Nipah virus studies in vitro and in vivo, including vaccine and pathogenesis studies, have utilized a virus isolate from the original Malaysian outbreak (NiV-M). To investigate potential differences between NiV-M and a Nipah virus isolate from Bangladesh (NiV-B), we compared NiV-M and NiV-B infection in vitro and in vivo. In hamster kidney cells, NiV-M-infection resulted in extensive syncytia formation and cytopathic effects, whereas NiV-B-infection resulted in little to no morphological changes. In vivo, NiV-M-infected Syrian hamsters had accelerated virus replication, pathology and death when compared to NiV-B-infected animals. NiV-M infection also resulted in the activation of host immune response genes at an earlier time point. Pathogenicity was not only a result of direct effects of virus replication, but likely also had an immunopathogenic component. The differences observed between NiV-M and NiV-B pathogeneis in hamsters may relate to differences observed in human cases. Characterization of the hamster model for NiV-B infection allows for further research of the strain of Nipah virus responsible for the more recent outbreaks in humans. This model can be used to study NiV-B pathogenesis, transmission, and countermeasures that could be used to control outbreaks.